(untitled) (Bangladesh Journal of Botany, 2020)
To compare the phytochemical and biological profiles, infusion and decoction extracts of dried Hibiscus sabdariffa calyces were prepared. Infusion extract had the highest phenolic content (292.42 ± 0.62 mg GAE/g extract) and antioxidant activity (TEAC = 3.09 ± 0.28). It also potently inhibited the activities of α-amylase (58.57 ± 1.4%), α-glucosidase (66.92 ± 2.5%) and 5-lipoxygenase (58.97 ± 1.17 μg/ml). All extracts showed weak cytotoxicity as tested on Vere monkey kidney cells.